The Century of Global Cities How Urbanisation is Changing the World and Shaping Our Future - Zevi, Andrea Tobia (2020)
Cities are gaining importance and influence worldwide. They sustain the global economy, set cultural trends, produce greenhouse gas emissions and consume energy; they attract migration flows and foster new political waves. While cities were supposed to be declining back in the 1980s, the globalised economy has established them as crucial world hubs leading billions of people on every continent, both at the top and the bottom of the social ladder, to move to cities. Today, global cities cry out for a more prominent role. But why and to what extent do they matter? Can they really stand alone in the global arena? How are they interacting with governments and multilateral organisations? From climate change to connectivity, from inequalities to migration: what is their contribution to key global challenges?